P387 Different rate of transmural remission between first and second line of biologic treatment in Crohn's disease. (30th January 2023) - De Sire, R; Rispo, A; Caiazzo, A; Testa, A; Nardone, O M; Guarino, A D; Olmo, O; Calabrese, G; Fierro, G; Toro, B; Cantisani, N M; Ferrante, M; et al.
Abstract: Background: Transmural remission in Crohn's disease (CD) has been associated with improved long-term clinical outcomes including reduced hospitalization, surgery, escalation of treatment, and a decrease in clinical relapse over endoscopic remission alone. Albeit transmural remission rate (TRR) in CD patients treated with anti-TNF drugs in first line has been well explored, data on TRR using vedolizumab (VDZ) or ustekinumab (UST) as second-line therapy for CD are still scarce. The aim of this study was to evaluate the TRR in CD patients in maintenance treatment, comparing adalimumab (ADA) in first line with VDZ/UST in second line. Methods: From 2018 to 2021 we performed a real world observational longitudinal study evaluating the TRR in all consecutive CD patients in a 2-years maintenance treatment with ADA in first line compared with those treated by VDZ or UST in second line. HBI, fecal calprotectin (FC), SES-CD, and bowel wall thickness (BWT) at ultrasound were analyzed in all patients at the baseline (T0) and after 2 years of maintenance treatment (T1). Clinical remission was defined when HBI was <4. Endoscopic remission was defined when SES-CD was <2. Transmural remission was defined when BWT was <3 mm at a "per-patient" analysis. In accordance with recent literature, laboratory remission was defined when FC was <94 ug/gr. Results: One hundred and forty-one CD patients (78 ADA, 31 VDZ, 32 UST) were included in the study. At T1, transmural remission rate was recorded in 39.7% of CD patients treated in first line with ADA, and in 22.5% and 18.7% for VDZ and UST, respectively, in second line (ADA vs VDZ/UST: p<0.05; VDZ vs UST: p 0.7). Endoscopic remission rate was 50% for patients treated in first line with ADA, and 32.2% and 31.2% for second line VDZ and UST, respectively (ADA vs VDZ/UST: p<0.05; VDZ vs UST: p 0.9). Laboratory remission rate was 53.8% for patients treated in first line with ADA, and 29% and 37.5% for VDZ and UST in second line, respectively (ADA vs VDZ/UST: p<0.05; VDZ vs UST: p 0.4). Clinical remission rate was 58.9% for patients treated in first line with ADA, and 45.1% and 40.6% for second line VDZ and UST, respectively (ADA vs VDZ/UST: p=0.057; VDZ vs UST: p=0.7). Conclusion: Our findings showed that in CD patients in maintenance treatment with biologics, ADA in first line showed a higher TRR compared with VDZ/UST in second line. Moreover, VDZ and UST showed similar TRR and other outcomes when used in second line.